Audit of start of anticoagulation treatment in inpatients. Issue 1 (January 1993) - Tan, G; Cohen, H; Taylor, F; Gabbay, J
Abstract : AIMS: To develop a method for evaluating the start of anticoagulation treatment in inpatients. METHODS: One hundred case notes were audited using a proforma based on local guidelines in accordance with British Society for Haematology recommendations. RESULTS: Confirmatory investigations were done in 93% and 79% of patients with symptomatic deep venous thrombosis and pulmonary embolism, respectively. Identification of patients' risk factors for anticoagulation by history taking and laboratory tests was often inadequate: baseline coagulation screen, platelet count, liver function and renal function tests were done in 52%, 95%, 70% and 87% of cases, respectively. There was a tendency to undertreat patients: 33% of the activated partial thromboplastin times (APTT) and 58% of the International Normalised Ratios (INR) were subtherapeutic. The heparin-warfarin crossover period was particularly problematic: 37% stopped heparin without an INR that day, or had an INR of less than 2. Microscopic haematuria was monitored occasionally. Of the 62 patients continuing anticoagulation, 72% were discharged with the final INR in the therapeutic range. At discharge, only 74% of patients had documented appointments for the anticoagulant Clinic, the period between discharge and appointment ranging from 0 to 12 days. Of the 25 cases with an appointment exceeding four days after discharge, only six (24%) had arrangements for an interim INR check. CONCLUSIONS: The experience allowed the proforma to become streamlined to a more practical, reliable, and valid tool for use elsewhere. Findings will be fed back to the hospital staff to promote practice improvements before closing the audit loop by re-evaluating practice. Further studies are in progress to identify barriers experienced by doctors in implementing the guidelines and problems in the process of referral to the anticoagulant clinic.